Pengaruh Iklan Obat terhadap Keinginan Membeli Konsumen pada Obat Bebas Resep - Benardi Atmadja; Andrew Dwiarto; Fritz Obed Simamora; Raynaldo Andhika; Septian Budhy Dharmawan (Universitas Prasetiya Mulya, 2019)
This research aims to investigate the effect of Direct to Consumer Advertising to Consumer’s purchase intention to OTC drugs, and what is the most variable that affecting consumer’s purchase intention. This research uses a quantitative method to 206 Indonesian respondents. It is found that there are two variables that affecting to consumer’s purchase intention which is health awareness and brand image. This study have a couple of limitation which is only one brand of OTC drugs and the profile of the respondent is Indonesian nationality and have used brand OTC drugs.